Matrix-assisted laser desorption/ionization–time of flight mass spectrometry: protocol standardization and database expansion for rapid identification of clinically important molds. (December 2017) - Paul, Saikat; Singh, Pankaj; Rudramurthy, Shivaprakash M; Chakrabarti, Arunaloke; Ghosh, Anup K
Aim: To standardize the matrix-assisted laser desorption ionization–time of flight mass spectrometry protocols and expansion of existing Bruker Biotyper database for mold identification.Materials & methods: Four different sample preparation methods (protocol A, B, C and D) were evaluated.Results: On analyzing each protein extraction method, reliable identification and best log scores were achieved through protocol D. The same protocol was used to identify 153 clinical isolates. Of these 153, 123 (80.3%) were accurately identified by using existing database and remaining 30 (19.7%) were not identified due to unavailability in database. On inclusion of missing main spectrum profile in existing database, all 153 isolates were identified.Conclusion: Matrix-assisted laser desorption ionization–time of flight mass spectrometry can be used for routine identification of clinically important molds.